Influence of seams in the mechanical properties of PLA produced with multiple extrusion modules - Sardinha, M.; Frutuoso, N.; Vicente, C. M. S.; Ribeiro, R.; Leite, M.; Reis, L. (Procedia Structural Integrity, 2020)
This work aims to provide research guidance for the development of multiple extrusion manufacturing, with the objective of reducing large parts manufacturing time. The manufacture of parts with multiple collaborative extrusion heads emerge as a potential solution to overcome the limitations of speed, cost, and scale of the conventional extrusion processes. The existence of multiple independent extrusion modules imposes the existence of intersections areas in parts. These intersections are treated as seams. Four different types of specimens made of PLA, differing in seam dimensions, were produced with two independent extrusion modules. Samples were subjected to a tensile test and results suggest that in material extrusion, the seams act in a part by creating a localized fragility preventing it from entering a plastic domain and diminishing its tensile properties. Seam dimensions have little influence on the tensile strength of specimens, with the average values varying between 49.16 MPa for samples with seam without overlap areas and 46.69 MPa in samples with a 10 mm overlap. Samples with 20 mm overlap have an average tensile strength of 48.99 MPa. This work concludes that the existence of seams could be considerate in the design stage of a product and that the development of multiple extrusion manufacturing, with the goal of reducing large parts manufacturing time without compromising geometrical accuracy is worthy of studying.